Pengembangan Bahan Ajar Cerita Rakyat Berbasis Komik Untuk Penanaman Kemampuan Literasi Siswa Sekolah Dasar Kabupaten Rejang Lebong - Ahmad Yuda Anggara (Universitas Bengkulu, 2020)
This research aimed to develop folklord teaching material based on comic and the effectifness in instilling elementary student literacy skill on Rejang Lebong. The research used research and development method (R&D). The subject on this research were the 5th grade student of elementary school number 85 on Rejang Lebong as control class, the 5th grade student of Al Latif Unggulan Aisyiyah on Rejang Lebong as first class experiment and the 5th grade student of elementary school number 10 on Rejamg Lebong as second experiment class. Based on result of this research and the explanation. In conclution that (1) the development of teaching material began with preliminary study through student and teacher interview. Then the interview result were adjusted to the theory and the observation become a draft model that would be validated by experts. Revised draft model would be tested in small scale and large scale.AFter that the final test product would be conducted by pretest and postest technique and the gain score would be analized. (2) folklore teaching material based on comic was effective to instill student literacy. g-score of the experiment class has 0.63 for kognitif aspect and 0.57 for psikomor aspect, while the g-score in control class has 0.16 for kognitif and psikomotor aspect.